2008
DOI: 10.1038/nrd2684
|View full text |Cite
|
Sign up to set email alerts
|

Genomic-scale prioritization of drug targets: the TDR Targets database

Abstract: The increasing availability of genomic data for pathogens that cause tropical diseases has created new opportunities for drug discovery and development. However, if the potential of such data is to be fully exploited, the data must be effectively integrated and be easy to interrogate. Here, we discuss the development of the TDRtargets.org database (http://tdrtargets.org), which encompasses extensive genetic, biochemical and pharmacological data related to tropical disease pathogens, as well as computationally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
238
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(240 citation statements)
references
References 28 publications
0
238
0
2
Order By: Relevance
“…Databases such as TDR targets (http://tdrtargets.org) gather information on putative targets for several pathogens including Plasmodium, providing tools for their prioritization in whole genomes depending on user queries (Aguero et al, 2008). The Protein Data Bank (www.pdb.org) is also a useful resource, providing data on proteins whose 3D-structures have been solved experimentally by using either X-Rays or NMR.…”
Section: Bioassays For Parasite Targetsmentioning
confidence: 99%
“…Databases such as TDR targets (http://tdrtargets.org) gather information on putative targets for several pathogens including Plasmodium, providing tools for their prioritization in whole genomes depending on user queries (Aguero et al, 2008). The Protein Data Bank (www.pdb.org) is also a useful resource, providing data on proteins whose 3D-structures have been solved experimentally by using either X-Rays or NMR.…”
Section: Bioassays For Parasite Targetsmentioning
confidence: 99%
“…Gene essentiality is also thought to be an important criteria for identification of therapeutic drug targets (Agüero et al, 2008). But there is a limitation to this approach as it fails to identify some targets such as hypoxanthine phosphoribosyl transferase as essential in Plasmodium falciparum (false negative) (Winzeler et al, 1999), while sometimes it yields false positives as in the case of dihydrofolate reductase in Leishmania major (Titus et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we have utilized a subtractive genomics approach to predict genes essential to C. jejuni through homology search against experimentally predicted essentiality data from C. jejuni and H. pylori in DEG, both of which belong to the epsilon class of proteobacteria. Significant advancements in genome sequencing and bioinformatics coupled with experimental data have shown that factors which are determinant of structural and molecular properties of proteins, such as molecular weight, subcellular localization, transmembrane prediction, and availability of 3D structure, can aid in prioritization of drug targets (Agüero et al, 2008) and maximize the likelihood of landing to the best therapeutic target against pathogen, considerably reducing the time and resources for developing such an agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, there is a partnership between TriTrypDB and GeneDB teams and both Databases should be maintained and updated evenly to keep a similar content (personal communication on the EuPathDB WorkShop 2009). The availability of the complete DNA sequence of the human and human pathogens genomes [31,53] associated with the heavy expansion of information on chemical structures of known drugs and three-dimensional structures of potential new drug targets enables rational drug design [54][55][56]. Comparative genomic studies allow the identification of molecules or biochemical pathways that have already been targeted successfully in other pathogens [30,31].…”
Section: Brucei T Cruzi L (L) Major L (L) Infantum and L (Vmentioning
confidence: 99%